LEGAL CERTIFICITY OF OWNERSHIP CERTIFICATES AS EVIDENCE IN RESOLUTION OF LAND OWNERSHIP DISPUTES (STUDY OF DECISION NUMBER 8/PDT.G/2020/PN LWK AND DECISION OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA NUMBER 3589 K/PDT/2022) - Tiyana Br. Situngkir, Anggis; Purba, Hasim; Siregar, Mahmul (Penerbit Lafadz Jaya, 2025)
Decision Number 8/Pdt.G/2020/Pn Lwk and Decision of the Supreme Court of the Republic of Indonesia Number 3589 K/Pdt/2022), found legal uncertainty of Land Ownership Certificates that have strong evidence of land ownership but in court were declared invalid, The problems in this study are, namely How is the guarantee of legal certainty in the Laws and Regulations concerning Land Ownership Certificates, what is the Position of Land Ownership Certificates issued by the National Land Agency in proving civil cases, how are the legal considerations and decisions of the panel of judges regarding the evidentiary power of land ownership certificates in Decision Number 8/PDT.G/2020/PN LWK and Decision of the Supreme Court of the Republic of Indonesia number 3589K/PDT/2022. Types of normative legal research (normative juridical) or library legal research., Normative juridical is research that refers to theories, doctrines, norms, principles, principles and legal rules contained in the legislation in Indonesia. The nature of the research used in this study is exploratory research (exploration or exploration), all collected, and conclusions drawn using deductive methods. The results of the study found that the legal certainty of land ownership certificates has an important role in the agrarian legal system in Indonesia. Through land registration and issuance of certificates, rights holders can obtain the legal certainty needed to protect their rights and prevent disputes. Land Ownership Certificates as evidence of letters have an important role in providing legal certainty and protection for rights holders. By meeting the requirements set, the certificate functions as strong evidence in the judicial process, the Decision of the Luwuk District Court and the Supreme Court of the Republic of Indonesia show the importance of legal certainty in land ownership. Land ownership certificates as proof of ownership must be based on accurate data and a legitimate process.